Robot pencari api dan penghindar rintangan - Aan Suherman (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2015)
Abstract - Fire search and obstacle avoidance robot are types of mobile robots that can find targets in the form of fire by tracing walls. For this robot, the navigation system uses navigation using walls. Navigation using walls is an algorithm to guide robots by navigating along walls. This system works by adjusting the distance from the wall to the robot. If a change occurs, the robot moves to adjust the distance again. This robot consists of several main components to support it when navigating through walls to reach the target. This robot consists of a flame sensor placed on the front that serves as a detector for targets in the form of fire. In addition to the flame sensor, three ultrasonic sensors are located on the left, front and right of the robot. These three ultrasonic sensors function as wall detectors. Based on the test, the percentage of success of the robot reaches the target of fire by tracing the wall of the right side is 100% in room II, in room III 70%, in room IV 70% Whereas by tracing the left wall, the percentage of success in room II is 60%, in room III 70%, in room IV 100%. The success percentage of robots reaching the target with the right search method is 80% and the left is 76.667%. Keyword : Navigation wall following, obstacle avoidance robot, mobile robot, target search robot in the form of fire